Diapause- and cold-induced remodeling of phospholipid composition in the biological membranes of the boreal fly, Drosophila lummei - Panalee Petcharat; Petra Berková; Petr Vodrážka; Martin Moos; Vladimír Košťál (Journal of Thermal Biology, 2026)

Approaches to quantify and manipulate insect hormone signals - Fernando G Noriega; Guy Bloch; Martin Moos; Petr Simek; Marek Jindra (Current Opinion in Insect Science, 2025)

A piRNA modulates the levels of 20-hydroxyecdysone in the ovary of the German cockroach - Judit Gonzalvo; Nuria Farrus; Jorge Escudero; Petra Berková; Martin Moos; Marcela Nouzova; Fernando G. Noriega; David Pujal; Josep Bau; Maria-Dolors Piulachs (Journal of Insect Physiology, 2025)

Pitfalls in insect cryoprotectant functional studies: A case study of myo-inositol in Drosopila lummei - Tomáš Štětina; Lukáš Kučera; Martin Moos; Jan Rozsypal; Vladimír Koštál (Journal of Insect Physiology, 2025)

Effects of pronounced seasonal turnover and intraspecific variation in leaf traits on specialization of insect herbivores associated with six Salicaceae hosts - Priscila Mezzomo; Jing V. Leong; Vaclav Pokorny; Leonardo Ré Jorge; Tereza Volfova; Petr Kozel; Petr Vodrazka; Carlo L. Seifert; Klára Aurová; Martin Moos; Marica T. Engström; Juha-Pekka Salminen; et al. (Oecologia, 2025)

Variation in induced responses in volatile and non-volatile metabolites among six willow species: Do willow species share responses to herbivory? - Priscila Mezzomo; Jing V. Leong; Petr Vodrážka; Martin Moos; Leonardo R. Jorge; Tereza Volfová; Jan Michálek; Paola de L. Ferreira; Petr Kozel; Brian E. Sedio; Martin Volf (Phytochemistry, 2024)

Evolution of white matter hyperintensity segmentation methods and implementation over the past two decades; an incomplete shift towards deep learning - Maryam Rahmani; Donna Dierker; Lauren Yaeger; Andrew Saykin; Patrick H. Luckett; Andrei G. Vlassenko; Christopher Owens; Hussain Jafri; Kyle Womack; Jurgen Fripp; Ying Xia; Duygu Tosun; et al. (Brain Imaging and Behavior, 2024)
This systematic review examines the prevalence, underlying mechanisms, cohort characteristics, evaluation criteria, and cohort types in white matter hyperintensity (WMH) pipeline and implementation literature spanning the last two decades. Following Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines, we categorized WMH segmentation tools based on their methodologies from January 1, 2000, to November 18, 2022. Inclusion criteria involved articles using openly available techniques with detailed descriptions, focusing on WMH as a primary outcome. Our analysis identified 1007 visual rating scales, 118 pipeline development articles, and 509 implementation articles. These studies predominantly explored aging, dementia, psychiatric disorders, and small vessel disease, with aging and dementia being the most prevalent cohorts. Deep learning emerged as the most frequently developed segmentation technique, indicative of a heightened scrutiny in new technique development over the past two decades. We illustrate observed patterns and discrepancies between published and implemented WMH techniques. Despite increasingly sophisticated quantitative segmentation options, visual rating scales persist, with the SPM technique being the most utilized among quantitative methods and potentially serving as a reference standard for newer techniques. Our findings highlight the need for future standards in WMH segmentation, and we provide recommendations based on these observations.

Simulated Herbivory Affects the Volatile Emissions of Oak Saplings, while Neighbourhood Affects Flavan-3-ols Content of Their Leaves - Freerk Molleman; Manidip Mandal; Anna Sokół-Łętowska; Urszula Walczak; Martin Volf; Soumen Mallick; Martin Moos; Petr Vodrážka; Andreas Prinzing; Priscila Mezzomo (Journal of Chemical Ecology, 2024)

Tasty rewards for ants: differences in elaiosome and seed metabolite profiles are consistent across species and reflect taxonomic relatedness - Marie Konečná; Martin Moos; Helena Zahradníčková; Petr Šimek; Jan Lepš (Oecologia, 2018)

Community structure of insect herbivores is driven by conservatism, escalation and divergence of defensive traits in Ficus - Martin Volf; Simon T. Segar; Scott E. Miller; Brus Isua; Mentap Sisol; Gibson Aubona; Petr Šimek; Martin Moos; Juuso Laitila; Jorma Kim; Jan Zima; Jadranka Rota; et al. (Ecology Letters, 2018)
Escalation (macroevolutionary increase) or divergence (disparity between relatives) in trait values are two frequent outcomes of the plant‐herbivore arms race. We studied the defences and caterpillars associated with 21 sympatric New Guinean figs. Herbivore generalists were concentrated on hosts with low protease and oxidative activity. The distribution of specialists correlated with phylogeny, protease and trichomes. Additionally, highly specialised Asota moths used alkaloid rich plants. The evolution of proteases was conserved, alkaloid diversity has escalated across the studied species, oxidative activity has escalated within one clade, and trichomes have diverged across the phylogeny. Herbivore specificity correlated with their response to host defences: escalating traits largely affected generalists and divergent traits specialists; but the effect of escalating traits on extreme specialists was positive. In turn, the evolution of defences in Ficus can be driven towards both escalation and divergence in individual traits, in combination providing protection against a broad spectrum of herbivores.

Sympatric lineage divergence in cryptic Neotropical sweat bees (Hymenoptera: Halictidae: Lasioglossum) - Patricia Landaverde-González; Humberto Moo-Valle; Tomás E. Murray; Robert J. Paxton; José Javier G. Quezada-Euán; Martin Husemann (Organisms Diversity & Evolution, 2017)